The Impact of Input Tariffs on Gender Inequality: An Empirical Study in Indonesia - Heldini, Noorish (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: Discrimination between male and female workers occurs because of the difference in the “endowment” and social and cultural norms, especially in developing countries. This study aims to examine the impact of input tariffs on the ratio of female workers who are differentiated, based on technology-intensity and the labor-intensive sector and the non-labor-intensive sector. Background Problems: Trade openness contributes to technological change so companies reallocate resources more efficiently and reduce discrimination. Previous studies have yielded ambiguous results regarding input tariffs and the ratio of female workers. Therefore this study attempts to estimate the impact of input tariffs on the ratio of female workers in Indonesia. Novelty: In contrast to the previous studies that did not include the lag-dependent variable, this study includes the lag variable female labor ratio as an exogenous variable in the estimation. Research Methods: Using FE-IV, panel data at the company level for the period from 2003 to 2015. Finding/Results: The estimation results show that trade openness can eliminate discrimination and increase the ratio of female workers. When firms are differentiated by their technology-intensity, the reduction in input tariffs leads to an increase in the ratio of female workers in medium and high technology-intensity firms, and non-labor-intensive firms, where the impact is the same between importing and non-importing firms. The estimation results show that trade openness can eliminate discrimination and increase the ratio of female workers entering the market. Conclusion: Trade openness can have both positive and negative impacts on Indonesian workers, especially female workers. To increase female labor participation, the Indonesian government needs to implement supporting policies, to improve equitable access to education for all citizens in Indonesia, needs to provide child-care facilities around office areas, flexibility in working hours for women, training and skills, and provide opportunities for women to occupy strategic positions.